2022
DOI: 10.1530/eje-21-1239
|View full text |Cite
|
Sign up to set email alerts
|

Association between domains of quality of life and patients with Klinefelter syndrome: a systematic review

Abstract: Klinefelter syndrome (KS) is the second-most prevalent chromosomal disorder in men, though late diagnosis is very common and 50-75% of men remain undiagnosed. Evidence suggests that men with KS have impaired Quality of Life (QoL) but research on how the diagnosis of KS is associated with different QoL domains and what factors influence patients’ QoL is limited. This study aimed to provide a systematic review of the published evidence on factors that influence QoL in men with KS. DESIGN: Systematic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
3
6
0
Order By: Relevance
“…Our results corroborate findings from multiple other studies that associate SCAs with excess morbidity and higher health care utilization . Men with 47,XXY, independent of a known clinical diagnosis, were more likely than controls to endorse a history of numerous medical and psychological conditions, most of which have been previously reported and serve as external validation of our results . We also observed worse self-reported health and well-being metrics among men with SCA, which is congruent with current research, in which lower QOL outcomes are widely reported in individuals with SCAs .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results corroborate findings from multiple other studies that associate SCAs with excess morbidity and higher health care utilization . Men with 47,XXY, independent of a known clinical diagnosis, were more likely than controls to endorse a history of numerous medical and psychological conditions, most of which have been previously reported and serve as external validation of our results . We also observed worse self-reported health and well-being metrics among men with SCA, which is congruent with current research, in which lower QOL outcomes are widely reported in individuals with SCAs .…”
Section: Discussionsupporting
confidence: 91%
“… 2 , 3 , 4 , 5 , 6 , 7 , 8 We also observed worse self-reported health and well-being metrics among men with SCA, which is congruent with current research, in which lower QOL outcomes are widely reported in individuals with SCAs. 8 , 31 , 32 In contrast, we did not find greater mortality, 3 , 5 , 33 perhaps because MVP does not capture deaths prior to enrollment; thus far, follow-up is relatively short, and the life expectancy of our controls was young (approximately 70 years), possibly reflecting worse health among US veterans. 34 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations